Nfat/calcineurin signaling promotes oligodendrocyte differentiation and myelination by transcription factor network tuning. - Weider, Matthias; Starost, Laura Julia; Groll, Katharina; Küspert, Melanie; Sock, Elisabeth; Wedel, Miriam; Fröb, Franziska; Schmitt, Christian; Baroti, Tina; Hartwig, Anna; Hillgärtner, Simone; Piefke, Sandra; et al. (Nature Communications, 2018)
Oligodendrocytes produce myelin for rapid transmission and saltatory conduction of action potentials in the vertebrate central nervous system. Activation of the myelination program requires several transcription factors including Sox10, Olig2, and Nkx2.2. Functional interactions among them are poorly understood and important components of the regulatory network are still unknown. Here, we identify Nfat proteins as Sox10 targets and regulators of oligodendroglial differentiation in rodents and humans. Overall levels and nuclear fraction increase during differentiation. Inhibition of Nfat activity impedes oligodendrocyte differentiation in vitro and in vivo. On a molecular level, Nfat proteins cooperate with Sox10 to relieve reciprocal repression of Olig2 and Nkx2.2 as precondition for oligodendroglial differentiation and myelination. As Nfat activity depends on calcium-dependent activation of calcineurin signaling, regulatory network and oligodendroglial differentiation become sensitive to calcium signals. NFAT proteins are also detected in human oligodendrocytes, downregulated in active multiple sclerosis lesions and thus likely relevant in demyelinating disease.
UnivIS-Import:2018-09-11:Pub.2018.med.IB.LPCIPDBI.nfatca

Publisher Correction: Nfat/calcineurin signaling promotes oligodendrocyte differentiation and myelination by transcription factor network tuning - Weider, Matthias; Starost, Laura Julia; Groll, Katharina; Küspert, Melanie; Sock, Elisabeth; Wedel, Miriam; Fröb, Franziska; Schmitt, Christian; Baroti, Tina; Hartwig, Anna; Hillgärtner, Simone; Piefke, Sandra; et al. (Nature Communications, 2018)
The originally published version of this Article omitted Tanja Kuhlmann and Michael Wegner as jointly supervising authors. This has now been corrected in both the PDF and HTML versions of the Article.
EVALuna2:35744

Sox10 Activity and the Timing of Schwann Cell Differentiation Are Controlled by a Tle4-Dependent Negative Feedback Loop - Aberle, Tim; Walter, Anna; Piefke, Sandra; Hillgärtner, Simone; Wüst, Hannah; Wegner, Michael; Küspert, Melanie (International Journal of Molecular Sciences, 2024)
The HMG-domain containing transcription factor Sox10 plays a crucial role in regulating Schwann cell survival and differentiation and is expressed throughout the entire Schwann cell lineage. While its importance in peripheral myelination is well established, little is known about its role in the early stages of Schwann cell development. In a search for direct target genes of Sox10 in Schwann cell precursors, the transcriptional co-repressor Tle4 was identified. At least two regions upstream of the Tle4 gene appear involved in mediating the Sox10-dependent activation. Once induced, Tle4 works in tandem with the bHLH transcriptional repressor Hes1 and exerts a dual inhibitory effect on Sox10 by preventing the Sox10 protein from transcriptionally activating maturation genes and by suppressing Sox10 expression through known enhancers of the gene. This mechanism establishes a regulatory barrier that prevents premature activation of factors involved in differentiation and myelin formation by Sox10 in immature Schwann cells. The identification of Tle4 as a critical downstream target of Sox10 sheds light on the gene regulatory network in the early phases of Schwann cell development. It unravels an elaborate regulatory circuitry that fine-tunes the timing and extent of Schwann cell differentiation and myelin gene expression.
CRIS-Team Scopus Importer:2024-06-07
Keywords: glia; HMG; Schwann cells; Sox10; transcriptional regulation

Transcription factor Zfp276 drives oligodendroglial differentiation and myelination by switching off the progenitor cell program - Aberle, Tim; Piefke, Sandra; Hillgärtner, Simone; Tamm, Ernst R.; Wegner, Michael; Küspert, Melanie (Nucleic Acids Research, 2022)
In oligodendrocytes of the vertebrate central nervous system a complex network of transcriptional regulators is required to ensure correct and timely myelination of neuronal axons. Here we identify Zfp276, the only mammalian ZAD-domain containing zinc finger protein, as a transcriptional regulator of oligodendrocyte differentiation and central myelination downstream of Sox10. In the central nervous system, Zfp276 is exclusively expressed in mature oligodendrocytes. Oligodendroglial deletion of Zfp276 led to strongly reduced expression of myelin genes in the early postnatal mouse spinal cord. Retroviral overexpression of Zfp276 in cultured oligodendrocyte precursor cells induced precocious expression of maturation markers and myelin genes, further supporting its role in oligodendroglial differentiation. On the molecular level, Zfp276 directly binds to and represses Sox10-dependent gene regulatory regions of immaturity factors and functionally interacts with the transcriptional repressor Zeb2 to enable fast transition of oligodendrocytes to the myelinating stage.
CRIS-Team Scopus Importer:2022-03-11

Zinc-finger transcription factor Zfp276 acts as a novel regulator of oligodendroglial differentiation - Aberle, Tim; Piefke, Sandra; Hillgärtner, Simone; Schimmel, M.; Tamm, E. R.; Wegner, Michael; Küspert, Melanie (GLIA, 2021)
CRIS-Team WoS Importer:2021-07-16